Pengaruh Pemberian Ekstrak Etanolik Daun Pandan Wangi (Pandanus amaryllifolius Roxb.) Terhadap Kadar Enzim Alp Pada Tikus Putih Yang Diinduksi Isoniazid Dan Rifampisin - Angga Adi Rahmawan; Supriyadi Supriyadi; Tri Wijayanti (Jurnal Farmasi Indonesia, 2016)
Pandan leaves are medicinal plants that contain alkaloids, saponins, flavonoids, tanins and poliphenols compounds that have high antioxidant activity and potential as hepatoprotective. This research was conducted to determine the effect of ethanol extract pandan leaves (Pandanus amaryllifolius Roxb.) on the rate of ALP in to determine potency extract ethanol pandan leave inhibit necrosis cell of liver in white rats isoniazid and rifampisin induced. This research was used thirty rats were divided in 6 groups. Group I as a normal group. Group II as a hepatotoxic group. Group III as a drug group was given Curcuma 3,6 mg/200 g BW. Group IV, V, and VI as the treatment group given test solution ethanol extract pandan leaves 8,64 mg/200 g BW, 17,28 mg/200 g BW and 25,92 mg/200 g BW for 28 days. All groups except group I were induced by isoniazid and rifampisin 10,8 mg/200 g BW. All groups on day 0, 14th and 28th set ALP rate. Results obtained were analyzed by One Way ANOVA test. The results showed that ethanol extract pandan leaves at a dose of 8,64 mg/200 g BW, 17,18 mg/200 g BW, and 25,92 mg/200 g BW can inhibit ALP in to determine potency ethanol extract pandan leave inhibit necrosis cell of liver in white rats isoniazid and rifampisin induced. Dose of the ethanol extract pandan leaves was the most effective is 25,92 mg/200 g BW.